2012
DOI: 10.5897/jmpr11.698
|View full text |Cite
|
Sign up to set email alerts
|

The studying effect of drought stress on germination, proline, sugar, lipid, protein and chlorophyll content in purslane (Portulaca oleracea L.) leaves

Abstract: Purslane (Portulaca oleracea L.) is one of the valuable medical plants. Drought also is one of the most important environment stresses that influences metabolism and growth of plant. The studying of physiological plant response rather than water stress can be influential equipment for understanding drought resistance mechanisms. In this study, the drought stress effects on germination and physiological characteristic of the medical plant (purslane) were studied. Drought imposed on polyethylene glycol (PEG) see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 19 publications
3
13
0
Order By: Relevance
“…Drought stress may also reduce leaf chlorophyll content, which is a critical factor in reducing plant growth and yield [26]. In the current study, selenium treatment (75 mg/L) at the vegetative stage alleviated the negative effects of drought stress by increasing chlorophyll accumulation, further suggesting the upregulation of photosynthesis.…”
Section: Discussionsupporting
confidence: 48%
“…Drought stress may also reduce leaf chlorophyll content, which is a critical factor in reducing plant growth and yield [26]. In the current study, selenium treatment (75 mg/L) at the vegetative stage alleviated the negative effects of drought stress by increasing chlorophyll accumulation, further suggesting the upregulation of photosynthesis.…”
Section: Discussionsupporting
confidence: 48%
“…Thus, P. grandiflora and B. scoparia had highest salt tolerance index as compared to other two species. The results of current investigation agreed with Chen et al [24] and Rahdari et al [25] where they observed that Proline accumulated significantly with consequent increase in level of salinity. Don et al [26] evaluated that the proline content increased in gerbera with increased salinity levels and this proline depict the adaptive response of gerbera to short term salinity.…”
Section: Electrolyte Leakage (%)supporting
confidence: 92%
“…A similar reduction in the Chl amount was registered in chickpea, Solanum lycopersicum, Triticum aestivum, Ricinus communi, and other plant species [3,[45][46][47][48]. A salt-induced reduction in the chlorophyll content could be attributed to impaired chlorophyll biosynthesis and/or increased chlorophyll degradation, although the impact of these processes varies in plant species [49]. The decrease in Chl content in pea corresponds with an increase of the Chl a/b ratio (Table 1), suggesting a reduction of the LHCII and a decrease of the number of granal thylakoids [50][51][52], i.e., having an influence on the organization of the thylakoid membranes.…”
Section: Discussionsupporting
confidence: 55%